2003
DOI: 10.1080/110241598750005930
|View full text |Cite
|
Sign up to set email alerts
|

Seton treatment of anal fistula: experience with a new modification

Abstract: The method is simple, therapeutic results are satisfactory, and patients tolerate the procedure well. We recommend it in any case in which total fistulectomy cannot be done because of the risk of incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 10 publications
2
39
0
1
Order By: Relevance
“…Table 4 shows the rates of incontinence after cutting seton treatment for each classification of fistula. 'Transsphincteric' includes transsphincteric, low and high, and [35] 13 ⁄ 21 Every second day Culp [26] 3 ⁄ 20 Patient moved seton several times daily Decanini-Terán et al [37] 0 ⁄ 42 Started 3 weeks postoperative; as patient tolerated Deshpande et al [30] 0 ⁄ 397 Every week Durgan et al [38] 2 ⁄ 10 Every 10 days Dziki and Bartos [39] 12 ⁄ 32 † Once a week Fasth et al [40] 0 ⁄ 7 Started a minimum of 3 months postoperative; 2-3 times weekly Flich Carbonell et al [41] 3 ⁄ 19 Not tighten postoperatively Gonzalez-Ruiz et al [43] 0 ⁄ 31 2-Week intervals Graf et al [44] 15 ⁄ 29 Once at 4 weeks postoperative Gurer et al [25] 0 [55] 0 ⁄ 53 Weekly Mohite et al [31] 0 ⁄ 114 New setons inserted weekly Qureshi et al [57] 2 ⁄ 4 Examined weekly; tightened if necessary Shukla et al [21] 8 ⁄ 155 Seton changed weekly Tahir [58] 5 ⁄ 9 Examined weekly; tightened as necessary Theerapol et al [59] 0 ⁄ 41 Patient to pull seton on a daily basis, one week postoperative Vatansev et al [61] 5 ⁄ 32 Tightened once in a period of 2 weeks Walfisch et al [62] 0 ⁄ 23 Once at 1 month postoperative Williams et al [63] 8 ⁄ 13 Patients followed regularly; tightened as necessary Zbar et al [22] 3 ⁄ 34 2-Week intervals Average rate 11.2% *Number of incidents of incontinence ⁄ number of patients.…”
Section: Classification Of Fistulamentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 shows the rates of incontinence after cutting seton treatment for each classification of fistula. 'Transsphincteric' includes transsphincteric, low and high, and [35] 13 ⁄ 21 Every second day Culp [26] 3 ⁄ 20 Patient moved seton several times daily Decanini-Terán et al [37] 0 ⁄ 42 Started 3 weeks postoperative; as patient tolerated Deshpande et al [30] 0 ⁄ 397 Every week Durgan et al [38] 2 ⁄ 10 Every 10 days Dziki and Bartos [39] 12 ⁄ 32 † Once a week Fasth et al [40] 0 ⁄ 7 Started a minimum of 3 months postoperative; 2-3 times weekly Flich Carbonell et al [41] 3 ⁄ 19 Not tighten postoperatively Gonzalez-Ruiz et al [43] 0 ⁄ 31 2-Week intervals Graf et al [44] 15 ⁄ 29 Once at 4 weeks postoperative Gurer et al [25] 0 [55] 0 ⁄ 53 Weekly Mohite et al [31] 0 ⁄ 114 New setons inserted weekly Qureshi et al [57] 2 ⁄ 4 Examined weekly; tightened if necessary Shukla et al [21] 8 ⁄ 155 Seton changed weekly Tahir [58] 5 ⁄ 9 Examined weekly; tightened as necessary Theerapol et al [59] 0 ⁄ 41 Patient to pull seton on a daily basis, one week postoperative Vatansev et al [61] 5 ⁄ 32 Tightened once in a period of 2 weeks Walfisch et al [62] 0 ⁄ 23 Once at 1 month postoperative Williams et al [63] 8 ⁄ 13 Patients followed regularly; tightened as necessary Zbar et al [22] 3 ⁄ 34 2-Week intervals Average rate 11.2% *Number of incidents of incontinence ⁄ number of patients.…”
Section: Classification Of Fistulamentioning
confidence: 99%
“…Christensen et al [35] 13 ⁄ 21 Durgan et al [38] 2 ⁄ 10 Dziki and Bartos [39] 4 ⁄ 21 4 ⁄ 4 4⁄ 7 Fasth et al [40] 0 ⁄ 5 0⁄ 2 García-Aguilar et al [42] 8 ⁄ 12 Graf [44] 15 ⁄ 29 Gurer et al [25] 0 ⁄ 4 0⁄ 12 0 ⁄ 1 Hämäläinen and Sainio [45] 18 ⁄ 30 2 ⁄ 2 2⁄ 3 Hamel et al [46] 0 ⁄ 12 Hasegawa et al [48] 11 ⁄ 22 2 ⁄ 3 2⁄ 3 Joy and Williams [51] 5 ⁄ 10 McCourtney and Finlay [53] 3 ⁄ 16 Mentes et al [54] 4 ⁄ 20 Qureshi et al [57] 2 ⁄ 4 Tahir [58] 5 ⁄ 9 Tocchi et al [60] 4 ⁄ 28 Vatansev et al [61] 5 ⁄ 32 Walfisch et al [62] 0 ⁄ 23 Williams et al [63] 8 ⁄ 13 Zbar et al [22] 3 Despite the difficulty in comparing the different reports, this study has identified some important points. First the global rate of incontinence was 12% when any kind of cutting seton was used.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent rates of incontinence vary widely (reported levels range from 0% to 82% (3,4)), while success rates range from 79% to 100% (3)(4)(5)(6)(7)(8)(9). The importance attached by patients to the possibility of having incontinence after treatment for a perianal fistula is reflected in an interesting article published in 2010 by Ellis (10), who concluded that most patients opt for sphincter-preserving techniques even though they are known to produce poorer results.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a seton has a recurrence rate of 0%-8%. Minor and major incontinence is 34%-64% and 2%-26%, respectively [5][6][7][8][9][10] . Many different methods for treating anorectal fistulae, particularly fistulae in which fistulotomy are contraindicated, have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%